Решите Срочно! Заранее спасибо. -9(8-х)-4х=-2 -5(-1+9)-5х=-1 -6(1-х)+4х=-4 -8(3+х)+х=4...

0 голосов
20 просмотров

Решите Срочно! Заранее спасибо.
-9(8-х)-4х=-2
-5(-1+9)-5х=-1
-6(1-х)+4х=-4
-8(3+х)+х=4
-6=-9(7+х)+4х


Алгебра (25 баллов) | 20 просмотров
Дано ответов: 2
0 голосов

1) -9 (8-x)-4x=-2 -72+9x-4x=-2 -72+5x=-2 5x=-2+72 5x=70 X=14 2) -5 (-1+9)-5x=-1 -5×8-5x=-1 -40-5x=-1 -5x=-1+40 -5x=39 -x=39÷5 X=-7.8

(14 баллов)
0

-5 (-1+9)-5x=-1

0

? Почему вы мне написали мой пример?

0

Извините, я по ошибке!

0 голосов

1)-9(8-х)-4х=-2
-72+9х-4х=-2
9х-4х=-2+72
5х=70
х=70÷5
х=14
2)-5(-1+9)-5х=-1
5-45-5х=-1
-5х=-1+45-5
-5х=39
х=39÷-5
х=- 7,8
3)-6(1-х)+4х=-4
-6+6х+4х=-4
10х=-4+6
10х=2
х=2÷10
х=0,2
4)-8(3+х)+х=4
-24-8х+х=4
-7х=4+24
-7х=28
х=28÷-7
х=-4
5)-6=-9(7+х)+4х
-6=-63-9х+4х
-6+63=-9х+4х
57=-5х
5х=57
х=57÷5
х=11,4

(227 баллов)